Grade 2 acute GVHD is a factor of good prognosis in patients receiving peripheral blood stem cells haplo-transplant with post-transplant cyclophosphamide. (3rd April 2021) - Chevallier, Patrice; Berceanu, Ana; Peterlin, Pierre; Garnier, Alice; Le Bourgeois, Amandine; Imbert, Berthe-Marie; Daguindau, Etienne; Mahé, Béatrice; Dubruille, Viviane; Blin, Nicolas; Touzeau, Cyrille; Gastinne, Thomas; et al.
Abstract: Background: The impact of acute graft versus host disease (GVHD) on survivals for patients receiving a haploidentical allogeneic stem-cell transplant (Allo-SCT) with peripheral blood stem-cells (PBSC) complemented by post-transplant cyclophosphamide (PTCY) is ill-known. Material and methods: This retrospective study included 131 patients who received a PBSC haplograft in order to precise the impact of acute GVHD on outcomes. There were 78 males and 53 females and the median age for the whole cohort was 59 years (range: 20–71). Thirty-five patients were allografted for a lymphoid disease and 96 for a myeloid malignancy, including 67 patients with acute myeloid leukemia (AML). Results: The cumulative incidence (CI) of day 100 grade 2–4 and 3–4 acute GVHD was 43.4 + 4.6% and 16.7 + 3.4%, respectively. The 2-year CI of moderate/severe chronic GVHD was 10.1 + 2.8%. The only factor affecting the occurrence of GVHD was GVHD prophylaxis. Indeed, CI of day 100 grade 2–4 (but not grade 3–4) acute GVHD was significantly reduced when adding anti-thymoglobulin (ATG) to PTCY. However, in multivariate analysis, grade 2 acute GVHD was significantly associated with better disease-free (HR: 0.36; 95%CI: 0.19–0.69, p  = .002) and overall (HR: 0.35; 95%CI: 0.1–0.70, p  = .003) survivals. The same results were observed when considering only AML patients. Conclusion: Acute grade 2 GVHD is a factor of good prognosis after PBSC haplotransplant with PTCY. Further and larger studies are needed to clarify the complex question of GVHD prophylaxis in the setting of haplo-transplant, especially that of combining ATG and PTCY.